Cancer cell killing using engineered intracellular antibody fragments - Chambers, J (2018)
Cancer is one of the leading causes of morbidity and death worldwide, with many either refractory to current therapy regimens or subsequently developing resistance. Novel targeted therapies are therefore needed. Acute T cell leukaemia (T-ALL) is an example of a malignancy without targeted therapies. It has a poor prognosis in adult patients and relapsed disease patients have only a 10% survival rate. T-ALL oncogenes include mutant RAS and aberrantly expressed LMO2, occurring in approximately 10-20% and 50% of cases respectively. There are currently no treatments specific for these oncogenes. Intracellular expression of single domain VH antibodies raised against these targets has been shown to inhibit tumour growth in leukaemic models. These antibody fragments can target and disrupt the effect of oncogenic proteins and their downstream complexes. The aim of this thesis was to potentiate the effect of these antibodies by linking them to a cytotoxic domain to destroy tumour cells upon antibody-antigen interaction. This thesis describes a novel adaptation to a method of targeted cancer cell killing known as Antibody-antigen Interaction Dependent Apoptosis (AIDA). The results of this study show the ability of two single domain antibodies (VH and VL) linked to the inactive apoptotic enzyme proCaspase 3 to elicit RAS antigen-specific, antibody-mediated cancer cell death. This effect requires both antibody fragments to bind at close epitopes for proximity auto-activation of the caspase 3 enzyme. This thesis also describes the development of a mammalian screening strategy for isolation of VL antibody fragments complementary to antigenbinding VH, and a method of in vitro culture and testing of AIDA in T cell lines and primary tumours. Subject to further progress in therapeutic delivery methods, this approach is anticipated to be widely applicable to cancers caused by many different oncogenic proteins, following the development of synergistic antigen-specific antibody fragments.